1984
DOI: 10.1007/bf00390656
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of enhanced harpacticoid (Copepoda) abundances around isolated seagrass shoots

Abstract: At a site in the Gulf of Mexico (29°54.6'N, 81°31.4'W) off the coast of northern Florida, harpacticoid copepod abundance is significantly enhanced around isolated "plants" (technically short shoots) of the seagrass Syringodium filiforme. Using inanimate mimics of seagrass short shoots, we demonstrate, in the field, that the enhanced abundance does not results from the presence of the plant as a living entity. Our experiments reveal a two-fold increase in bacterial biomass around both short shoots and mimics; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The correspondence between distributional patterns of benthic organisms with fine sediment distributions has been attributed to the passive accumulation of settling larvae and sediments in areas that are sheltered or have weak currents and depressions on the sea floor (Verwey 1952, Kristensen 1957, Carriker 1961, Fager 1964, Scheltema 1974, Levin 1984, Butman 1987. Moreover, the stability can be also attributed to the presence of tubicolous organisms (Woodin 1978, Eckman 1979, Atkins 1983, Hsieh & Chang 1991, or that of seagrass beds (Virnstein et al 1983, Peterson et al 1984, Thistle et al 1984. Nowell & Church (1979) showed that the density of O. fusiformis tubes required to stabilize the sediment must be around 14 500 ind.…”
Section: Discussionmentioning
confidence: 99%
“…The correspondence between distributional patterns of benthic organisms with fine sediment distributions has been attributed to the passive accumulation of settling larvae and sediments in areas that are sheltered or have weak currents and depressions on the sea floor (Verwey 1952, Kristensen 1957, Carriker 1961, Fager 1964, Scheltema 1974, Levin 1984, Butman 1987. Moreover, the stability can be also attributed to the presence of tubicolous organisms (Woodin 1978, Eckman 1979, Atkins 1983, Hsieh & Chang 1991, or that of seagrass beds (Virnstein et al 1983, Peterson et al 1984, Thistle et al 1984. Nowell & Church (1979) showed that the density of O. fusiformis tubes required to stabilize the sediment must be around 14 500 ind.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that meiofauna are found to enter the water both passively and actively requires consideration of the adaptive significance of these water column excursions. Possible short-term advantages of meiofaunal emergence include finding mates and copulating (Hicks 1988), avoiding crowded conditions, i, e. density-dependent migration ( S e~c e & Bell 1987), and feeding in the benthic boundary layer (Decho 1986), in surficial sediments, or near structures where food resources may be enhanced (Thistle et al 1984, Eckman 1985. The major disadvantages of entering the water-column include transport to unfavorable areas (Palmer & Gust 1985) and possible increased predation by epibenthic and natant predators due to the enhanced visibility/availability of meiofauna once they are above the sediments (Robertson & Howard 1978, Magnhagen & Widerholm 1982, Marinelli & Coull 1987, Palmer 1988.…”
Section: Introductionmentioning
confidence: 99%
“…Fonseca et al 1983). Although to our knowledge there has been only one experimental study specifically addressing hydrodynamic influence on faunal structure, distribution, or behavior in seagrass systems (Thistle et al 1984), the possible significance of these phenomena has not escaped wider notice (Orth 1977, Fonseca et al 1982, 1983, Thayer et al 1984. The effect of currents on filter-feeding organisms commonly found in seagrass beds has long been recognized (e.g.…”
Section: Introductionmentioning
confidence: 99%